Osteopenia Is Associated with Shorter Survival in Patients with Intrahepatic Cholangiocarcinoma - Atsushi Miki; Yasunaru Sakuma; Jun Watanabe; Kazuhiro Endo; Hideki Sasanuma; Takumi Teratani; Alan Kawarai Lefor; Joji Kitayama; Naohiro Sata (Current Oncology, 2023)
Background: The prognostic importance of osteopenia in patients with intrahepatic cholangiocarcinoma (ICC) undergoing hepatectomy is unclear. The aim of this study was to evaluate the impact of osteopenia on survival in patients with ICC. Methods: A total of 71 patients who underwent hepatectomy at Jichi Medical University between July 2008 and June 2022 were included in this study. Non-contrast computed tomography scan images at the eleventh thoracic vertebra were used to assess bone mineral density. The cutoff value was calculated using a threshold value of 160 Hounsfield units. Overall survival curves were made using the Kaplan–Meier method and the log-rank test was used to evaluate survival. The hazard ratio (HR) and 95% confidence interval (CI) for overall survival were calculated using Cox’s proportional hazard model. Results: In multivariable analysis, osteopenia (HR 3.66, 95%CI 1.16–14.1, p = 0.0258) and the platelet–lymphocyte ratio (HR 6.26, 95%CI 2.27–15.9, p = 0.0008) were significant independent factors associated with overall survival. There were no significant independent prognostic factors for recurrence-free survival. Conclusions: Preoperative osteopenia is significantly associated with postoperative survival in patients with ICC undergoing hepatectomy.